INFILTRASI LDII DALAM PENAFSIRAN AL-QUR’AN: Studi Analisis Interpretasi LDII Terhadap Ayat-Ayat Imamah - Umar Zakka (Sekolah Tinggi Agama Islam Hasan Jufri Bawean, 2021)
Indonesian Islamic Dakwah Institute abbreviated (on Indonesia language) as LDII is an institution or orgnozation on Indonesia that in engaged in Islamic dakwah activities in the form of social activities as well as formal or non formal education. One of the theaching in this institution is the imam concept. Every muslim, especially members of this institution, is obliged to obey the imam, namely the leader of the LDII itseflt. They use the evidence in al-Qur’an surah al-Isra’ verse 71 and surah al-Nisa’ verse 59, as well as the hadith from Imam Ahmad. The word “imam” in the verse by LDII refers to their leader who is recognized as an imam. From the result of a critical analysis of LDII’s interpetation and understanding of the obove verses that none of the scholars interpretations interpret as understood by LDII. Therefore, the result of the LDII interpretation of the verses corcerning of the imam are wrong and heretical.